TWITAUTOLOGY: NEOLOGISM IN K-POP FANBASE ON TWITTER - Sheilma 'Arivah Zayyan; Elsa Lailatul Marfu'ah; Maharani Surya Samodra; Hanifah Nur Salsabilla; Chika Amalinda; Diah Ayu Istiqomah (Fakultas Komunikasi, Sastra, dan Bahasa, 2023)
Every fandom has a unique pattern of language usage to communicate with one another. Different fandoms, of course, affect their language patterns respectively, because the neologisms that are formed can represent the identity of each fandom. K-Pop fandom itself has a wide community all over the world that is connected through a virtual network. Twitter is a virtual data network platform used by many members of the K-Pop fandom. To find out about at what level neologism in K-Pop fandom on Twitter is formed, the data are collected by sampling tweets of Twitter users who are part of three K-Pop boy group fandom namely Seventeen, Stray Kids and Treasure, who use Vocabulary, Orthography, Grammar and Pragmatic in their tweets using descriptive qualitative methods. The findings reveal that some language aspects in K-Pop fandom share different knowledge from the regular language. The results show that the K-Pop fandom community tend to create neologisms based on the identity of the specific idol they like, not only within the K-Pop fandom itself, which makes it unique. This research provides insight that neologism exists in the K-Pop fandom community on twitter to provide the community members an easier way to communicate without having to explain the context.